Нові підходи до радіо- та хіміосенсибілізації за допомогою інгібіторів протонної помпи крізь призму патернів мікрооточення пухлинних клітин - Гладких, Ф.В.; Кулініч, Г.В.; Золотарьова, Т.Г. (Ukrainian Journal of Radiology and Oncology, 31(2), 230-242. https://doi.org/10.46879/ukroj.2.2023.230-242, 2023)
Chaotic and improper angiogenesis in the tumor tissue causes deficit in O2 perfusion in tumors, a decreased capacity to deliver nutrients and remove metabolism products from cells, creating preconditions for the formation of hypoxic and alkaline microenvironment which drives tumor progression, invasion and metastases. Recent studies have shown that the use of proton pump inhibitors (PPIs) increases sensitivity of the tumor cells that are resistant to cytotoxic drugs and radiation therapy. Purpose – to provide insight into the modern data on the possibilities of the use of proton pump inhibitors for overcoming radio- and chemoresistance. Materials and methods. The selection of publications was performed in such databases as Pubmed, eBook Business Collection, Clinical Key Elsevier, Cochrane Library in which the data on the ways of overcoming radio- and chemoresistance of tumor cells using PPIs were described. At the first stage, the search of literature sources was carried out by the following keywords: radioresistance, proton pump inhibitors, tumor cell microenvironment. At the second stage, the abstracts of the articles were studied, and those publications that did not match the criteria of our work were excluded. At the third stage, full texts of the selected articles were studied for relevance and eligibility to be included in the references. Results and discussion. The modulation of the acidic tumor cell microenvironment is a prospective direction of antitumor treatment. The abnormal pH-gradient between the extracellular environment and the cell cytoplasm is mediated by different ion/proton pumps, including vacuolar H+-ATPase, Na+/H– exchangers, monocarboxylate transporters, carbonic anhydrases, etc. Several studies have revealed that PPIs inhibit not only the H+/K+-ATPase in gastric parietal cells, but also the vacuolar H+-ATPase (V-ATPase) overexpressed in tumor cells. The addition of PPIs to treatment regimen has demonstrated effectiveness in tumor processes of different localization, including those in colorectal cancer, ovarian cancer, lung cancer, pancreatic cancer, prostate cancer, and breast cancer. Conclusions. The obtained data from the analysis of literature sources indicate the potential of conducting preclinical and clinical trials of the effectiveness of PPIs as the new radio- and chemosensitizing drugs in Ukraine.
New approaches to radio- and chemosensitization using proton pump inhibitors through the lens of tumor cell microenvironment patterns
Hladkykh, F., KulinichН., & Zolotarova , T. (2023). New approaches to radio- and chemosensitization using proton pump inhibitors through the lens of tumor cell microenvironment patterns. Ukrainian Journal of Radiology and Oncology, 31(2), 230-242. https://doi.org/10.46879/ukroj.2.2023.230-242
Keywords: tumor cell microenvironment; radioresistance; proton pump inhibitors; radiation therapy; chemosensitization; radiosensitization